Biofluid mechanics an introduction to fluid mechanics, macrocirculation, and microcirculation - Rubenstein, David A.; Yin, Wei; Frame, Mary D. (Academic Press series in biomedical engineering, 2015)
Biofluid Mechanics: An Introduction to Fluid Mechanics, Macrocirculation, and Microcirculation shows how fluid mechanics principles can be applied not only to blood circulation, but also to air flow through the lungs, joint lubrication, intraocular fluid movement, renal transport among other specialty circulations. This new second edition increases the breadth and depth of the original by expanding chapters to cover additional biofluid mechanics principles, disease criteria, and medical management of disease, with supporting discussions of the relevance and importance of current research. Calculations related both to the disease and the material covered in the chapter are also now provided